Emotion-based multimedia retrieval and delivery through online user biosignals: multichannel online biosignals towards adaptative GUI and content delivery - V. Vinhas (2009)
Affective computing and multichannel multimedia distribution have gathered the time and investment of industry and academics. The proposed system merges such domains so that ubiquitous system can be enhanced through online user emotion assessment based on user's biosignals. It was used IAPS as a emotional library for controlled visual stimuli and biosignals were collected in real-time - heartbeat rate and skin conductance - in order to online assess the user's emotional state through Russell's Circumplex Model of Affect. In order to improve usability and session setup, a distributed architecture was used so that software models might be physically detached. The conducted experimental sessions and the validation interviews supported the system's efficiency not only in real-time discrete emotional state assessment but also considering the emotion inducing process. The next logic step consists in replicating the achieved success in multi-format multimedia contents without the need of pre-defined restricted emotional metadata.